Normative Juridical Analysis of Conflicts of Interest in Inheritance Disputes Under the Indonesian Civil Code - Zahwa Ayni Sabilah; Nuraini Fitri Ramadhani (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Inheritance disputes represent one of the most frequent forms of civil conflict within Indonesian legal practice, often arising from competing claims among heirs and differing interpretations of inheritance law. This study aims to examine the legal framework governing inheritance under the Indonesian Civil Code, identify common forms of conflicts of interest among heirs, and assess the effectiveness of existing dispute resolution mechanisms. The research employs a normative juridical method using statutory and conceptual approaches to analyze relevant legal provisions and doctrines. The findings reveal that although the Civil Code provides a relatively comprehensive structure for inheritance regulation, practical implementation still exposes significant legal gaps that enable prolonged conflicts of interest. Litigation mechanisms, while legally binding, tend to be time-consuming and costly, making them less efficient in resolving family-based disputes. Consequently, alternative dispute resolution methods, particularly mediation and negotiation, offer more flexible and humane solutions, although their effectiveness remains limited due to structural and cultural constraints. The study suggests the need for strengthening non-litigation mechanisms and improving legal awareness to minimize recurring inheritance conflicts and promote more sustainable dispute resolution practices.